Performance of micronutrient coated urea on growth and yield of Amaranthus gangeticus - Mat Daud, Nurhana (2015)
Urea is an important fertilizer as the source of nitrogen. The low efficiency of nitrogen is a problem for the crop growth. Nitrogen is lost through nitrate (NO3) leaching, ammonia (NH3) volatilization and denitrification. The high rate of urea hydrolysis also can increase the rate of nitrogen loss. This problem caused the lower rate of urea efficiency and to overcome this problem, micronutrient coated urea is used to increase the rate of efficiency of urea, to reduce the loss of urea and to increase the growth of the Amaranthus gangeticus. In this study, five treatments were used, namely: urea; urea+Copper; urea+Zinc; urea+Boron; and urea+Zinc+Copper+Boron. Parameters taken in this study were the nitrogen content in the soil and plant, dry weight and fresh weight. Experimental design used in this experiment was Randomized Complete Block Design and each treatment has four replications. Each replicate was arranged in the randomized position of different block. This study was being conducted using top soil Munchong series, which was taken from Ladang 2, UPM. The duration of study is 4 weeks. The plant used in this experiment was amaranth (Amaranthus gangeticus) grown with applied fertilizer. The data of nitrate (NO3), ammonium (NH4+), and total nitrogen were collected every week after the fertilizer application. The data were statistically analyzed using Analysis of Variance (ANOVA) and the mean compared using Least Significant Differences (LSD) Test. Expected results by using micronutrient coated urea are the increase in the growth of the plant and uptake of nitrogen by plant in the form of nitrate (NO3) and decrease in the amount of nitrogen released.